Consistent patterns of elevational change in tree taxonomic and phylogenetic diversity across Malesian mountain forests. (13th June 2013) - Culmsee, Heike; Leuschner, Christoph; Richardson, James
Abstract Aim In order to investigate the relative importance of ecological (habitat specialization) and biogeographical (speciation, geographical dispersal limitation) processes as causes of non‐random spatial distribution of tree species in the mountain forests of Malesia, we analysed the elevational change in the taxonomic and phylogenetic diversity of tree assemblages in different biogeographical subregions. Location Malesia (Borneo, Java, Sulawesi and the Philippines). Methods Tree inventory data of 12 old‐growth forests from a wide elevational range (650–3080 m a.s.l.) were taxonomically harmonized and standardized (50 random draws of 245 individuals each per plot), and the phylogeny of 204 genera was resolved and scaled to its evolutionary origin. The taxonomic and phylogenetic diversities were calculated using effective generic measures, and the diversity patterns analysed by regression, ordination and classification. Results The primary factor determining the diversity patterns of the tree assemblages was elevation, whereas the influence of region was surprisingly low. This results in common elevational patterns in taxonomic and phylogenetic community structure across western and central Malesia. The major clades of the contemporary mountain forest trees must therefore have evolved before the formation of the Malay Archipelago in its present form (sympatric speciation). Taxonomic richness and phylogenetic diversity exhibited opposite trends with elevation. Generic richness decreased linearly with elevation; the phylogenetic structure of high‐elevation forests revealed overdispersion, indicating convergent trait evolution towards higher elevations, whereas the submontane and colline assemblages showed clustering with a considerable number of confamilials. The upper montane forests of Borneo and Sulawesi were characterized by the dominance of Southern Hemisphere conifers, which differentiated them from lower‐elevation communities. Main conclusions Our results indicate that ecological, evolutionary and biogeographical processes (environmental filtering, sympatry and long‐distance dispersal) have shaped the contemporary community structure of Malesian mountain forests. Wallace's Line may represent a significant barrier between the lowland tree floras of Borneo and Sulawesi, but this is not true for those at higher elevations. The uniqueness of high‐elevation forests in terms of their high phylogenetic diversity and of their unusual structure calls for a high priority in conservation programmes.